What is the impact of using design and technology pedagogy to support the attainment of 21st-century skills? - Kelaotswe Archie Galeboe; Richie Moalosi; Yaone Rapitsenyane; Victor Ruele (Discover Education)
Abstract Effective pedagogy, when harnessed by educators, can empower students to become creative problem solvers, innovative thinkers, and lifelong learners capable of thriving in the dynamic and interconnected world of the 21st-century. This study explores the impact of the teachers' pivotal role in using Design and Technology (D&T) teaching and learning activities and underscores the importance of these 21st-century skills. These skills are not just desirable but crucial for success in the modern world. It also highlights the crucial role of educators in equipping students for the challenges of the future. Furthermore, the study examines the pedagogical approaches and instructional strategies employed within D&T education in Botswana to facilitate the attainment of 21st-century skills. The study adopted a case study design which integrated the use of a survey and lesson observations to gather data from students, teachers and school heads about D&T pedagogy, the teacher’s ability to use teaching and learning methods and the impact on 21st-century skills. The study findings indicate that when teachers create dynamic learning environments and accord students opportunities to engage in authentic, experiential learning experiences, there is the cultivation of 21st-century skills such as critical thinking, creativity, communication, collaboration, adaptability, and ethical responsibility. By harnessing the power of D&T teaching and learning activities, educators can empower students to become lifelong learners, innovative problem-solvers, and responsible global citizens poised to shape the future. The study provides insights into various approaches to classroom teaching and learning of D&T pedagogy, which can foster 21st-century skills.